Numerical investigation into cavitating flow around a NACA66 hydrofoil with DCM models. Issue 6 (March 2019) - Sun, L G; Guo, P C; Zheng, X B; Yan, J G; Feng, J J; Luo, X Q
Abstract: Unsteady cavitating flow is difficult to be predicted accurately with traditional RANS turbulence model, especially cavities shedding and evolution from sheet cavity to cloud cavity. In order to determine an appropriate numerical setup for accurate and reliable simulations of cavitating flow, the unsteady-state cavitating flow simulations are performed with the Zwart cavitation model accompanying with the DCM(Density correction model) model based on the RNG k-ε turbulence model after grid convergence test. The details about pressure distribution and cavities evolution around the hydrofoil show that the used models predict the cavities shedding frequency well, the pressure distribution along chord is quasi-periodic. Due to the dynamic of the shed cavities, periodic lift and drag coefficient are pretty clear with both positive and negative values. The cavities formation, breakup, shedding and collapse in a cycle are also presented.